Auxin-regulated timing of transition from vegetative to reproductive growth in rapeseed (Brassica napus L.) under different nitrogen application rates - Hao, Pengfei; Lin, Baogang; Ren, Yun; Hu, Hao; Xue, Bowen; Huang, Lan; Hua, Shuijin (Frontiers in Plant Science, 2022)
Accelerating the differentiation of floral meristem (FM) from shoot apical meristems (SAM) which determines the conversion from vegetative to reproductive growth is of great significance for the production of rapeseed (Brassica napus L.). In this research, the mechanisms of different nitrogen (N) application rates (low N, N1; normal N, N2; and high N, N3) on different FM development stages triggering the regulation of FM differentiation genes through the auxin biosynthetic and signal transduction were investigated. We found that the stage of FM differentiation, which was identified through a stereomicroscope and scanning electron microscope, came 4 and 7 days earlier under high N rate than under normal and low N levels, with the seed yield increased by 11.1 and 22.6%, respectively. Analysis of the auxin and its derivatives contents showed that the main biosynthesis way of auxin was the indole acetaldehyde oxime (IAOx) pathway, with 3-Indole acetonitrile dramatically accumulated during FM differentiation. At the same time, an obvious decrease of IAA contents at each FM differentiation stage was detected, and then gradually rose. Results of the expression of genes involved in auxin biosynthesis, auxin signaling transduction, and FM identification under five FM differentiation stages and three nitrogen application rates showed that genes involved in auxin biosynthesis were regulated before the FM differentiation stage, while the regulation of FM identity genes appeared mainly at the middle and later periods of the five stages, and the regulation level of genes varied under different N rates. Taken together, a high nitrogen rate could accelerate the initiation of FM differentiation, and auxin involved a lot in this regulation.